Study of Fertility in some Varieties of Radish (Raphanus sativus l.) and their Hybrids - Prasad Kalpana; Dayal N. (International Journal of Research in Chemistry and Environment (IJRCE), 2011)
Different varieties of radish (Raphanus sativus L.) were studied on some parameters like days to flower, pollen fertility, mean number of ovules / pistil, seed and siliquae set and fertilization value to understand the genotypic difference between them. Some of their F1 hybrids were found to be superior in these parameters in comparison to their parents.